Employment of micropatterned hydrogels to regulate the redox status of mesenchymal stem cells - Lee, Melissa Kao Hui (2018)
A large amount of effort is being put toward engineering and mimicking the cell microenvironment in hopes of greater understanding toward cellular processes in vivo. The use of hydrogels especially is a common method used to imitate the extracellular matrix (ECM) which is essential in influencing cell characteristics and activity. Stem cell activity has been linked to changes in the stem cell microenvironment and one example is the adjustments in stem cell oxidative state as a result of changes to the ECM. This project investigates the independent effects of substrate stiffness and cell spreading area, which usually accompany one another, on intracellular ROS production by creating a controlled microenvironment through the use of biomimetic hydrogels of various stiffness and micropattern sizes. It was observed that isolating cell spreading and substrate stiffness ultimately leads to the same effect of reduced Ras homolog gene family, member A (RhoA) activation which subsequently allows for elevated Ras-related C3 botulinum toxin substrate 1 (Rac1) activity, which is a major binding partner in NOX generation of ROS. The decoupling of substrate stiffness and spreading area to identify ROS-generating pathways in stem cells could contribute to development of new regenerative medicine techniques that exploit stem cells.